THE RELATIONSHIP BETWEEN AUTHORITARIAN PARENTING AND STRESS LEVELS AMONG INDONESIAN ADOLESCENTS: A CROSS-SECTIONAL STUDY - Anugrah, Fira Mutiara; Manalu , Lisbet Octovia (Journal of Community Mental Health and Public Policy, 2025)
Background: Parenting is important for psychological development in adolescents. Each type of parenting has a different impact on the emotional and social development of children. Parents who implement authoritarian parenting will make children tend to be difficult to control and not confident in their decisions. Purpose: To determine the relationship between authoritarian parenting and stress levels in adolescents. Method: This study used quantitative research with a cross-sectional approach. The number of samples was 139 respondents using random sampling techniques. The research instrument used an authoritarian parenting questionnaire and a daily stress response scale (DSRS). The statistical test used in this study was the Spearman rank test. Results: A total of 80 (56.6%) respondents had an authoritarian parenting pattern with a moderate category and 76 (54.7%) respondents had a stress level with a moderate category. The Spearman rank correlation test produced a P value of 0.000 (P <0.05) which means there was a significant relationship between authoritarian parenting and stress levels in adolescents. This means that the more authoritarian parenting was applied, the higher the level of stress experienced by adolescents. Conclusion: There is a significant relationship between authoritarian parenting and stress levels in adolescents with a positive relationship direction. Abstrak Latar Belakang: Pola asuh orang tua sangat penting terhadap perkembangan psikologis pada remaja. Setiap jenis pola asuh memiliki dampak yang berbeda-beda terhadap perkembangan emosional dan sosial anak. Orang tua yang menerapkan pola asuh otoriter akan membuat anak cenderung susah diatur dan tidak percaya diri atas keputusannya. Tujuan: Mengetahui hubungan pola asuh otoriter dengan tingkat stres pada remaja. Metode: Penelitian ini menggunakan penelitian kuantitatif dengan pendekatan cross sectional. Jumlah sample 139 responden dengan menggunakan teknik random sampling. Instrumen penelitian menggunakan kuesioner pola asuh otoriter dan daily stress response scale (DSRS). Uji statistik yang digunakan pada penelitian ini yaitu uji Spearman rank. Hasil: Sebanyak 80 (56,6%) responden memiliki pola asuh otoriter dengan kategori sedang dan 76 (54,7%) responden memiliki tingkat stres dengan kategori sedang. Uji korelasi spearman rank menghasilkan nilai P 0,000 (P<0,05) yang berarti terdapat hubungan yang signifikan antara pola asuh otoriter dengan tingkat stres pada remaja. Hal ini berarti bahwa semakin pola asuh otoriter yang diterapkan, semakin tinggi tingkat stres yang dialami oleh remaja. Kesimpulan: Terdapat hubungan yang signifikan antara pola asuh otoriter dengan tingkat stres pada remaja dengan arah hubungan yang positif.